LOW-COST TIMBER BRIDGES FOR RURAL AREAS: A FIELD SURVEY AND RECOMMENDATIONS OF INTEREST - Criado, Tayla C.; da S. Ribas, Amauri [UNESP]; Molina, Julio C. (FapUNIFESP (SciELO), 2024)
Timber bridges in Brazil, intended for rural roads and rural areas, present several problems due to the lack of design, structural calculation, and periodic maintenance by municipal administrations. This study evaluated a total of 10 timber bridges with a deck of sawn planks connected by nails to natural round beams, aiming to identify their main pathologies and provide minimum pre-sizing values for the used sections. The bridges were inspected on-site to measure the parts and identify the main problems. Subsequently, based on the Manual de Projeto e Construção de Pontes de Madeira and ABNT NBR 7190-1 (2022), we verified whether the diameter of the round beams found on site was adequate from the point of view of structural sizing using an Excel spreadsheet. Most of the analyzed bridges had spans of up to 15 m and problems related to the degradation of the timber and metal connections, reducing their useful life. As a result, the main construction recommendations for bridges are the use of timber treated with chromated copper arsenate (CCA) and galvanized connections to prevent corrosion. The use of the proposed pre-sizing tables is recommended to ensure minimum calculation values, considering the design vehicle classes and the minimum dimensions for the timber sections. This study aims to guide Brazilian municipal administrations and other interested parties in the construction of timber bridges for rural areas, obtaining safe, low-cost, and highly durable structures.